HIV Testing in Publicly Funded Settings, National Health Interview Survey, 2003–2010. (January 2016) - Tan, Cheryl; Van Handel, Michelle; Johnson, Christopher; Dietz, Patricia
Objective: We determined whether or not HIV testing in publicly funded settings in the United States increased after 2006, when CDC recommended expanded HIV screening in health-care settings for all people aged 13–64 years. Methods: We analyzed 2003–2010 National Health Interview Survey data to estimate annual national percentages of people aged 18–64 years who were tested for HIV in the previous 12 months. Estimates were calculated by setting (publicly funded, yes/other) and stratified by sex. Test settings were categorized as publicly funded based on the contribution of public funds for HIV testing. We used logistic regression modeling to assess statistical significance in linear trends for 2003–2006 and 2006–2010, adjusting for age, race/ethnicity, and health insurance coverage. Using model parameters for survey year, we calculated the estimated annual percentage change (EAPC) in HIV testing as the difference in the model-predicted testing prevalence between baseline and first post-baseline years, divided by baseline prevalence. Results: During 2006–2010, the percentage of women tested for HIV in publicly funded settings increased significantly from 1.9% in 2006 to 2.4% in 2010 (EAPC=6.9%, p =0.008) and the percentage tested in other settings remained fairly stable, from 9.7% in 2006 to 9.6% in 2010 (EAPC=–0.5%, p =0.708). During the same period, the percentage of men tested for HIV in publicly funded settings increased, but not significantly, from 1.5% in 2006 to 1.9% in 2010 (EAPC=5.3%, p =0.110) and the percentage tested in other settings decreased significantly from 7.5% in 2006 to 6.2% in 2010 (EAPC=–4.4%, p =0.001). Conclusion: Although HIV testing in publicly funded settings increased among women during 2006–2010, testing rates remained low, and no similar increase occurred among men. As such, all test settings should increase HIV screening, particularly for men.